SELF-SERVICE APPLICATION PROGRAM INVENTORY AT XYZ USING MICROSOFT VISUAL FOXPRO 9.0. - Ahmad Fauzi Romdhoni; Ire Puspawardani, SKom, MMSI (Jurnal Sistem Informasi, 2010)
This scientific writing beisi of an application program inventory at a supermarket company. This application is made to simplify data recording incoming goods, the goods out and goods available in the warehouse and ensuring data security. And also to simplify searching data warehouse so that reports to the CEO will be more quickly available. In this paper the author only uses fictional data because the author wants to build an inventory application programs that are so general that can be customized with a company that wants to build this inventory application program.